2014
DOI: 10.1128/jvi.03516-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Contemporary G2P[4] Human Rotaviruses Cocirculating in a Single U.S. Community: Footprints of a Globally Transitioning Genotype

Abstract: Group IMPORTANCELittle is known about the diversity of cocirculating G2 rotaviruses and how their evolution may undermine the effectiveness of rotavirus vaccines. To expand our understanding of the potential genetic range exhibited by rotaviruses circulating in postvaccine communities, we analyzed part of a collection of rotaviruses recovered from pediatric patients in the United States from 2010 to 2011. Examining the genetic makeup of these viruses revealed they represented three segregated groups that did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

15
35
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 65 publications
(67 reference statements)
15
35
2
2
Order By: Relevance
“…Strains RVA/Human-wt/BRA/ SC19868/2011/G2P [4] (for VP1) and RVA/Human-wt/BRA/ ES16238/2009/G2P [4] (for VP3) showed close phylogenetic relationship with RVA/Goat-tc/BGD/GO34/1999/G6P[1] animal strain (97% identity). Similar results were recently described for G2P [4] RVA strains detected in USA and Italy (Dennis et al, 2014;Giammanco et al, 2014). As happens in other countries, available data regarding animal RVA strains is still poor and make it difficult to study the origin of this kind of animal-like genome segment incorporation into human RVA strains.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Strains RVA/Human-wt/BRA/ SC19868/2011/G2P [4] (for VP1) and RVA/Human-wt/BRA/ ES16238/2009/G2P [4] (for VP3) showed close phylogenetic relationship with RVA/Goat-tc/BGD/GO34/1999/G6P[1] animal strain (97% identity). Similar results were recently described for G2P [4] RVA strains detected in USA and Italy (Dennis et al, 2014;Giammanco et al, 2014). As happens in other countries, available data regarding animal RVA strains is still poor and make it difficult to study the origin of this kind of animal-like genome segment incorporation into human RVA strains.…”
Section: Discussionsupporting
confidence: 86%
“…4 and 5) suggesting the occurrence of reassortment events among strains. This discrepancy with the results from Dennis et al (2014) and results obtained in our study might be related with the fact that samples analyzed in the current study were detected in different Brazilian regions, sometimes geographically distant, and strains detected during a relatively long time period were analyzed (2005)(2006)(2007)(2008)(2009)(2010)(2011). On the other hand, similar results regarding NSP4 and VP3 encoding gene were observed for Brazilian G2P [4] strains, these two genes were the most divergent among the eleven RVA genes (Figs.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…Therefore, to determine which mutated nucleotide at the reverse primer End9 binding sites is responsible for amplification failure with Beg9/End9, a series of reverse primers were designed to replace the single original nucleotide or degenerate base at each of the four point mutation positions in End9. Surprisingly, whatever the position the mutated nucleotide was in, it barely influenced The recently established unified nomenclature system for the VP7 genes of human G2 RVAs includes four major lineages (I-IV) and at least three sublineages (IVa-1 to IVa-3 for lineages IV), among which lineage IV included most of the globally prevalent G2 strains [15][16][17][18]. In addition, the VP7 genes of porcine G2 RVAs, which were thought to share a common evolutionary origin with human RVAs [19], were classified more recently as belonging to lineage V [17].…”
mentioning
confidence: 98%
“…The genotype of segments encoding the viral proteins VP7-VP4-VP6-VP1-VP2-VP3-NSP1-NSP2-NSP3-NSP4-NSP5/NSP6 is represented by the acronym Gx-Px-Ix-Rx-CxMx-Ax-Nx-Tx-Ex-Hx, where x is an integer. Whole-genome sequencing has shown that human RVs with the genotype constellation of G1/G3/G4/G9/G12-P [8]-I1-R1-C1-M1-A1-N1-T1-E1-H1 or G2-P[4]-I2-R2-C2-M2-A2-N2-T2-E2-H2 are globally dominant (18)(19)(20)(21)(22)(23)(24)(25). Several neonatal RV strains have been identified with overall genotype constellations that are similar to those of the globally dominant strains, with the exception of their P genotypes.…”
mentioning
confidence: 99%